1995
DOI: 10.1007/bf00661331
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of lead absorption from soil affected by smelter emissions

Abstract: The purpose of this study was to assess the oral bioavailability of lead in soil collected from a former smelter site in Sandy, Utah, USA. Sprague-Dawley rats (approximately 4 weeks of age, 5 of each sex in group) were given either soil lead or lead acetate mixed in a purified diet (AIN-93G ™) at four different concentrations for 31 consecutive days. Food consumption measurements were used to compute mean daily lead exposures for the soil lead and lead acetate groups. The lead acetate treatment yielded higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 7 publications
5
43
1
2
Order By: Relevance
“…Bioavailability predictions vary widely for lead in soil. One study suggests that default available fractions could be as large as 30% (Schoof et al 1995). Overwhelming evidence suggests that toxicity of Pb is reduced over time by natural attenuation such as the complexation of Pb into an unavailable form (Skerfving and Bergdahl 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Bioavailability predictions vary widely for lead in soil. One study suggests that default available fractions could be as large as 30% (Schoof et al 1995). Overwhelming evidence suggests that toxicity of Pb is reduced over time by natural attenuation such as the complexation of Pb into an unavailable form (Skerfving and Bergdahl 2007).…”
Section: Discussionmentioning
confidence: 97%
“…This is nearly double compared to the bioavailable Pb found in mine waste soils from Butte, Montana [68]. Schoof et al [70] categorized the Pb into three groups based on a mineralogical assessment: (i) soluble and very soluble [Pb carbonate (9%), Pb oxide (4%), manganese Pb oxide (3%), and iron Pb oxide (10%)]; (ii) moderately soluble [Pb arsenate (15%), Pb iron sulfate (6%), and Pb sulfate (17%)]; and (iii) slightly soluble [Pb phosphates (29%)]. Further analysis of phosphate phases by electron microprobe revealed that 83% of the Pb existed as chloropyromorphite, about 15% as an amorphous mixture of metals, and 2% as Pb-bearing apatite.…”
Section: In Vivo Studiesmentioning
confidence: 95%
“…Schoof et al [70] assessed the relative bioavailability of Pb in soils collected from a former smelter site in Sandy, Utah. Sprague-Dawley rats were fed either soil Pb or Pb acetate in a purified diet at four different concentrations for 31 consecutive days.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Um dos primeiros estudos in vivo, realizado com ratos, relacionou a biodisponibilidade com a espécie de Pb em solos 31 24 . Os autores 32 do estudo atribuíram os valores mais elevados de biodisponibilidade à presença nas amostras de espécies mais solúveis (como carbonatos, arsenatos e a fase amorfa).…”
Section: Ensaios De Biodisponibilidade In Vivounclassified
“…A variação do pH do estômago também foi utilizada para avaliar as condições do estômago quando em jejum (pH 1,3) e logo após a ingestão de alimentos (pH 4,0), e também em pH 2,5 usado como valor médio. Os resultados foram comparáveis aos de biodisponibilidade obtidos em ratos por Freeman et al 31 (10%) e Schoof et al 32 (36%), principalmente na fase gástrica e com pH 2,5. Para a fase intestinal, devido a maior complexidade, tanto da solução simulada quanto das condições intestinais dos ratos, os resultados apresentam as maiores diferenças relativas entre métodos e pouca reprodutibilidade.…”
unclassified